Which Phonetic Features Should Pronunciation Instructions Focus on? An Evaluation on the Accentedness of Segmental/Syllable Errors in L2 Speech - Gao, Zhiyan; Weinberger, Steven (Research in Language, 2018)
Many English language instructors are reluctant to incorporate pronunciation instruction into their teaching curriculum (Thomson 2014). One reason for such reluctance is that L2 pronunciation errors are numerous, and there is not enough time for teachers to address all of them (Munro and Derwing 2006; Thomson 2014). The current study aims to help language teachers set priorities for their instruction by identifying the segmental and structural aspects of pronunciation that are most foreign-accented to native speakers of American English. The current study employed a perception experiment. 100 speech samples selected from the Speech Accent Archive (Weinberger 2016) were presented to 110 native American English listeners who listened to and rated the foreign accentedness of each sample on a 9-point rating scale. 20 of these samples portray no segmental or syllable structure L2 errors. The other 80 samples contain a single consonant, vowel, or syllable structure L2 error. The backgrounds of the speakers of these samples came from 52 different native languages. Global prosody of each sample was controlled for by comparing its F0 contour and duration to a native English sample using the Dynamic Time Warping method (Giorgino 2009). The results show that 1) L2 consonant errors in general are judged to be more accented than vowel or syllable structure errors; 2) phonological environment affects accent perception, 3) occurrences of non-English consonants always lead to higher accentedness ratings; 4) among L2 syllable errors, vowel epenthesis is judged to be as accented as consonant substitutions, while deletion is judged to be less accented or not accented at all. The current study, therefore, recommends that language instructors attend to consonant errors in L2 speech while taking into consideration their respective phonological environments.